2013
DOI: 10.1111/apt.12397
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: a herbal preparation of myrrh, chamomile and coffee charcoal compared with mesalazine in maintaining remission in ulcerative colitis - a double-blind, double-dummy study

Abstract: SUMMARY BackgroundThe herbal treatment with myrrh, dry extract of chamomile flowers and coffee charcoal has anti-inflammatory and antidiarrhoeal potential and might benefit patients with UC. Aminosalicylates are used as standard treatment for maintaining remission in ulcerative colitis (UC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 35 publications
(41 reference statements)
1
48
0
9
Order By: Relevance
“…Relapse rates were 45% in the 5-ASA treatment group 53% in the herbal treatment group which was interpreted as non-inferiority in maintenance therapy of UC patients [96].…”
Section: Therapies With Natural Compounds (Anthocyanins Curcuma and mentioning
confidence: 93%
“…Relapse rates were 45% in the 5-ASA treatment group 53% in the herbal treatment group which was interpreted as non-inferiority in maintenance therapy of UC patients [96].…”
Section: Therapies With Natural Compounds (Anthocyanins Curcuma and mentioning
confidence: 93%
“…In der nun erfolgten Leitlinienaktualisierung hat der Stellenwert komplementärmedizinischer Behandlungsverfahren weiter zugenommen. Neue hochwertige kontrolliert-randomisierte Studien ermöglichten die Ergänzung der bereits vorhandenen Empfehlungen um weitere komplementärmedizinische Therapieverfahren [3,4,5]: Yoga (Empfehlung 6.2.6) und ein pflanzliches Kombinationspräparat aus Myrrhe, Kamillenblütenextrakt und Kaffeekohle (Empfehlung 6.2.10) - für das es in Deutschland ein zugelassenes traditionelles Arzneimittel gibt - können nun leitlinienkonform komplementär in der Behandlung eingesetzt werden. Innerhalb des Unterkapitels «Mind-Body Verfahren» wird weiterhin auch die Lebensstilmodifikation thematisiert - ein besonders vielversprechender Therapieansatz, da er eine Vielzahl von Ansätzen aus der Komplementärmedizin enthält.…”
Section: Tableunclassified
“…Their flowers contain antioxidant and anti-inflammatory compounds such as bisabolol, chamazulene, apigenin, and luteolin [60] . Two random double-blind controlled studies on UC patients found that a chamomile preparation which also contained myrrh and coffee charcoal was as effective as mesalamine [61,62] . However, since the preparation contained many components, one cannot assign the beneficial effects to chamomile alone.…”
Section: Chamomilementioning
confidence: 99%